Stent Embolization Mimicking Acute Myocardial Infarction. (July 2021) - Huda, Syed Arqum; Kahlown, Sara Akram; Pathmanathan, Anojan; Farooqi, Muhammad Saad; Charlamb, Mark
Venous thromboembolism is associated with significant morbidity and mortality if left untreated. Anticoagulation is the cornerstone of treatment. Venous stents are a relatively newer entity that are increasingly being used to treat venous stenosis/occlusion. It is a safe procedure, but complications include vein rupture, arterial puncture, retroperitoneal bleeding, and in-stent thrombosis. Stent migration is a rare but potentially fatal complication. We present a case of venous stent embolization to the heart that presented as a non-ST segment elevation myocardial infarction.